Desempenho produtivo e econômico da Tilápia do nilo (O. niloticus) cultivada em tanques-rede nos períodos de inverno e verão, no rio do Corvo-Paraná - Alexandre Filho, Luiz (2008)
This project aimed to evaluate the performance and economic viability of fish creation in net cages as an alternative to improve life quality of the producers from Corvo River (Parana, Brazil) with minimum environmental impact and great sustainability. The research involved water quality monitoring considering the physic-chemical parameters and evaluation of zootechnical and economical indexes to three storage density in net cages with 100, 150 and 200 fish m-3 in summer and winter cultivation. The species used was Oreochromis niloticus of Thailandese strain, submitted to the sex reversal process. There were used 14,850 juvenile fish in the summer and 8,910 in the winter with 57 and 99 g of weight respectively, and distributed in 6.0 m³ useful cages, being 15 in summer and 09 in winter. The trial period of the summer was 84 days and 140 in winter; however, to final biomass calculation in the summer the weights from 130 days were used. The diet was composed by extruded commercial food, one with 32% PB for the first 30 days and another with 28% PB until the slaughter. The collects of limnological variables were done each thirty days in sub-surface layers, in a longitudinal transect inside the cage. Data of electrical conductivity and pH (digital potentiometers), water temperature daily monitored with maximum and minimum thermometer, dissolved oxygen, and transparency were obtained. The data from the limnological evaluation were submitted to an exploratory analysis through the descriptive statistics, and for the zootechnical and economic evaluation the variance analysis by GLM process were applied, followed by multiple comparison of average using the Tukey test (p<0.05). The physical chemical indicators for both periods were adequate to the limits of the studied specie, except in winter when the average temperature of 20.99°C influenced the results. The production cost structure used in the study was followed by the methodology of Production Operational Cost and as profitability indicators the Gross Revenue and Operating Profit. Analyzing the final zoothecnical performance of two seasons, it was observed that there was no difference (p<0.05) among the three densities in the two periods for final and daily average weight when analyzed separately. Survival rates during the summer showed differences (p<0.05) among treatments, and the lowest rate was for treatment with the highest density (79.99%), while treatments with lower density had the highest rate survivors (94.57%). Comparing the summer and winter period, it was found that there is a difference (p<0.05) for the obtained average weights in the same space-time cultivation. Fish reared in the summer showed a better performance than in the winter (460.40 grams and 367.76 grams respectively) with daily average weight gain of 5.60 g day-1 during the summer, and 3.58 g day-1 in winter. Differences were found (p<0.05) when it was examined the final biomass and feed intake, and the increases were rising as density was increased. The increase in consumption in summer has a direct influence on reducing the apparent food conversion, so that there was difference (p<0.05) for the three densities between the two periods. When it was analyzed the economic indicators in both periods, there was a difference (p<0.05) for all studied variables. The total operational cost (per kg of fish) in the summer period was R$ 2.19 and R$ 1.55 in the winter and the Operating Profit per kg of fish produced was higher in winter (R$ 0.95) than in the summer (R$ 0.31). It was concluded that increased density did not influenced the performance of the fish, therefore, it can establish that a density of 150 fish m-3 for the summer period and 200 fish m-3 for the winter can be used and that the production of the tilapia Nile in cage is economically viable for both periods.